FORMATION OF THE LOGISTICS SUBSYSTEM OF PRODUCT DISTRIBUTION - MEISH, Alla; YADUKHA, Sergey (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article highlights the transformational trends of the market environment, under which the product distribution model is gaining more and more importance. The explanation for this is the need for manufacturers and sellers to adapt to the needs of consumers and increase the efficiency of their satisfaction, to build systems of distribution and exchange of goods, to develop integrative inter-industry and inter-sectoral connections, to improve the quality of institutional relations. It was concluded that the issue of product distribution and the formation of its logistics subsystem is the object of numerous scientific studies, the main emphasis of which is given to the processes of marketing, technical-technological, information-communication and other support, while adhering to the interests of all market participants – manufacturers, sellers, consumers. The functional aspects of the formation of the logistics subsystem of product distribution have been determined. The distribution system unites a number of product supply chains and thereby qualitatively responds to changes in consumer preferences and ensures a high degree of their satisfaction. The establishment of product distribution has clear signs of creating a complete management system using mechanisms and approaches that primarily take into account technological and information and communication transformations. The characteristics of the fundamental differences of the logistics subsystem from other elements of enterprise management in the context of the features of product distribution are given. The speed of movement of products from the producer to the consumer, while often bypassing the retailer, becomes a decisive factor in establishing stable commodity-money relations. Accordingly, the formation of the logistics subsystem should take into account the numerous features of product distribution and become part of the general mechanism of enterprise management.
Keywords: product distribution; logistics; sales; enterprise; market